A new Hemigrammus Gill from upper rio Paraná system, Southeastern Brazil (Characiformes: Characidae) - Marinho, Manoela M. F. [UNESP]; Carvalho, Fernando R.; Langeani, Francisco [UNESP]; Tatsumi, Flá Vio L. (Magnolia Press, 2008)
Hemigrammus parana is described from the upper rio Paraná system, in the area of influence of the Ilha Solteira reservoir in states of Mato Grosso do Sul, Minas Gerais and São Paulo, southeastern Brazil. The new species differs from all congeners by the combination of the following characters: absence of humeral spot; presence of a roughly triangular or rectangular conspicuous black caudal spot, extending from base to tip of middle caudal-fin rays, its greatest depth at base of caudal-fin rays; and anal-fin rays iii-iv, 18-23. Copyright © 2008 Magnolia Press.
Keywords: Neotropical region; Rio Grande; South America; Taxonomy